Insulin glucose infusion versus nebulised salbutamol versus combination of salbutamol and insulin glucose in acute hyperkalaemia in the emergency room: protocol for a randomised, multicentre, controlled study (INSAKA) - Patrick Rossignol; Matthieu Legrand; Emmanuel Montassier; Loic Lemoine; Jean Benoit Hardouin (BMJ Open)
Introduction Hyperkalaemia is a common electrolyte disorder and can be life-threatening. In the emergency room (ER), interventions aim to protect patients from the immediate dangers of elevated serum potassium by redistributing potassium ions from the bloodstream into the cells via intravenous insulin or nebulised beta2-agonists. However, to date, evidence for acute management of hyperkalaemia is limited. The aim of this randomised controlled trial is therefore to compare three strategies, namely insulin/glucose intravenous infusion, nebulised salbutamol or a combination of nebulised salbutamol and insulin/glucose intravenous infusion to reduce serum potassium concentration at 60 min as a first-line treatment in patients admitted to the ER with serum potassium concentrations superior or equal to 6 mmol/L.Methods and analysis INSAKA is a prospective, multicentre, controlled, open-label, parallel-group, randomised in a 1:1:1 ratio clinical trial. Patients will be eligible for randomisation if they have serum potassium concentrations superior or equal to 6 mmol/L measured in the ER. Patients will receive either: (1) 10 mg of nebulised salbutamol, (2) 10 units of short-acting insulin in an intravenous bolus with 500 mL of 10% glucose or (3) 10 units of short-acting insulin in an intravenous bolus with 500 mL of 10% glucose combined with 10 mg of nebulised salbutamol. The primary endpoint will be the mean change in the absolute serum potassium level from baseline to 60 min measured in mmol/L. We plan to include 525 patients.Ethics and dissemination The INSAKA trial will be conducted in accordance with the International Council on Harmonization Good Clinical Practices. All trial documents and procedures have been reviewed and approved by the Ethics Committee Sud Méditerranée III (approval ID number: 19.07.16.36428). The results will be actively disseminated through peer-reviewed journals, conference presentations, social media, broadcast media, print media and the internet.Trial registration EudraCT number: 2019-002710-39, Clinicaltrials.gov identifier: NCT04012138.